The Role of Play in Child Assessment and Intervention - Silvia Salcuni (Frontiers Research Topics, 2017)
Play is a ubiquitous and universal aspect of early childhood. Although it may take different forms throughout development and across cultures, decades of research have found play to be related to important, positive outcomes. Play provides children with valuable cognitive, emotional, and interpersonal learning opportunities. It can act as a mode of communication for young children and allows them to practice ways of managing complex interpersonal interactions. Specific aspects of play, such as children's creativity in pretend play, have been associated with resilience and coping. The significance of play in childhood has led to its frequent use in the assessment of child development and in the implementation of child and parent-child psychological and educational interventions. Historically, however, the validity and efficacy of these interventions have not been rigorously evaluated. Further, few assessment and intervention models have included parents, teachers, and other key caregivers, but have focused only on the child. This Research Topic will bring together the most current literature on the use of play in child assessment and intervention.